Conceptual modelling of complex production systems - Perši, Nenad (Array, 2008)
Summary: Complex system dynamics, structure and behaviour performances call for a wide range of methods, algorithms and tools to reach a model capable of finding optimal performing parameters. In the modelling process, it is up to the analyst to select the appropriate combination of methods, algorithms and tools to express significant system performances. Such a methodology for designing complex systems should be based upon conceptual modelling to perform a sensitive analysis of different system levels and views, allowing system representations for developing computer models.Complex systems, such as business systems with a continuous-discrete production process, require a well organised supply chain highly reactive to production assortment changes. Aligning two different production components distinctive in their behaviour is especially delicate at the production parameters transition point. Such system performances require distinctive designing methods that can follow the double nature of the production process behaviour in accordance with their entities dynamics caused by assortment changes. Consequently, such systems need different conceptual presentations for their purpose to be realized from different views and aspects